Aplicação da espirometria durante teste padrão de exercício progressivo em esteira para avaliação da troca gasosa respiratória de equinos da raça árabe - Watanabe, Marcos Jun [UNESP]; Silveira, V. F. [UNESP]; Machado, L. P. [UNESP]; Yonezawa, L. A. [UNESP]; Kohoyagawa, A. [UNESP]; Thomassian, A. [UNESP] (My University, 2009)
The current study evaluated equine gas exchange responses through spirometry, by measuring oxygen uptake (VO2), carbon dioxide production (VCO2), respiratory exchange ratio (R) and maximum oxygen uptake (VO2max) of Arabian horses during a standard incremental exercise test performed on a high-speed treadmill. Six clinically healthy Arabian horses were submitted to a standard incremental exercise test, performed on a high-speed treadmill at a 6% slope, and initial speed of 1,8 m.s-1 for 5 minutes, then 4,0 m.s-1 for 3 minutes, 6,0 m.s-1 for 2 minutes and 8,0 m.s-1, 9,0 m.s-1, 10,0 m.s-1 and 11,0 m.s-1 for one minute for each of these speed. The end of the exercise test was defined as the point in which the horse was no longer able to keep pace with the treadmill. Gas exchange was measured through respiratory analyses horse mask on the last 10 seconds at the end of each speed transition and at 1, 2 and 3 minutes after the end of the exercise, defined as experiment moments. During exercise, it was noticed an increase on both VO2 and VCO2 with linear relationship between exercise and speed. Arabian horses VO2max was 114,9 mL.kg-1.min-1. The respiratory exchange ratio increased over 1,0 by the speed of 9,0 m.s-1, indicating the preponderance of the anaerobic metabolism, and remains at a high level on the post-exercise period.
Application of spirometry during standard incremental exercise test on treadmill for respiratory gas exchange evaluation of Arabian horses
Keywords: Aerobic capacity; Equine; Oxygen uptake; Respiratory system; Equidae